Efficient Excavation and Support Cooperation Technology for Surrounding Rock of Deep Buried Long-Distance and Large Section Gob-Side Roadway: A Case Study - Houqiang Yang; Changliang Han; Nong Zhang; Xudong Li; Yitao Liu; Wentao Liu; Kai Song; Yuxin Guo; Wei Yao (Geofluids)
The gob-side roadway technology is widely used in coal mining in China, as it can improves the recovery rate of coal resources and alleviate the shortage of mining replacement. However, it is still difficult to control the stability of surrounding rock in gob-side roadway under deeper mining depth and more complex stress environment. With the auxiliary transportation roadway 30207 (ATR 30207) of the Muduchaideng Coal Mine as engineering background, this paper introduces the engineering case of gob-side roadway characterized by deep buried, long-distance, and large section. Through comprehensive methods, we studied and put forward the efficient excavation-support cooperation technology for surrounding rock of gob-side roadway. The research shows that the head-on cutting of gob-side roadway causes the stress to transfer and gradually adjust in the heading face to form a steady-state advanced abutment stress field. The coupling effect of the advanced abutment stress and the lateral abutment stress of goaf are the main reasons for repeated hole collapse of anchor cable drilling in solid coal rib, development and expansion of the roof separation fracture, and the low excavation speed. Supposed that upon the heading face support is completed, the next excavation-support cycle is quickly started during the early stage of stress adjustment, and the time effect can be fully utilized to alleviate the disturbance intensity of the advanced abutment stress in the heading face, as well as reduce the damage of rock mass. This paper puts forward the time-effect collaborative control countermeasures of the roof and rib in gob-side roadway of “hole collapse anchor cable of solid coal rib lag construction and waits for pressure relief and rapid excavation-support cycle in the heading face.” Engineering practice shows that the mine pressure behavior of roadway roof and solid coal rib is effectively controlled, and the roadway forming speed is greatly improved, which can provide reference for the efficient excavation-support design of gob-side roadway under the conditions of deep buried, long-distance, and large section in similar deep mines.